2013
DOI: 10.1111/aos.12200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low versus high fluidic settings on the efficacy and safety of phacoemulsification

Abstract: . Purpose:  To compare intraoperative efficiency and postoperative outcomes of cataract surgery with low and high fluidic settings. Methods:  In this prospective, randomized, single‐blinded study, 114 eyes of 57 patients were operated with low fluidic settings for one eye (group I) and high fluidic settings for the other eye (group II). Efficiency was judged as metred surgery time, effective phacoemulsification time (EPT) and the amount of balanced salt solution used. Visual outcome and endothelial cell count … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 21 publications
3
23
1
Order By: Relevance
“…This is consistent with previous studies confirming the relationship between phaco tip and phacoemulsification efficiency [22]. In any case, the EPT values achieved with both 20G and 21G tips in our series were consistently lower than those reported for conventional phacoemulsification cataract surgery with other platforms [12] [13], as previously mentioned. Schriefl et al [12] showed that a significant decrease in EPT was achievable with a 21G phaco tip by switching from low to high fluidic settings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies confirming the relationship between phaco tip and phacoemulsification efficiency [22]. In any case, the EPT values achieved with both 20G and 21G tips in our series were consistently lower than those reported for conventional phacoemulsification cataract surgery with other platforms [12] [13], as previously mentioned. Schriefl et al [12] showed that a significant decrease in EPT was achievable with a 21G phaco tip by switching from low to high fluidic settings.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, median values of EPT of 3.15 and 5.00 s were found when using the 20G and 21G phaco tips, respectively. These values are consistently lower than those reported for conventional phacoemulsification cataract surgery with other platforms [12] [13]. Likewise, the EPT values obtained in our series are close tothose reported by other authors combining femtosecond laser cataract surgery platforms with phaco systems [14]- [16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Somewhat surprisingly, increasing the aspiration rate did not statistically improve efficiency in this series. This is in contrast to our previous work9,10,1315 and clearly is a feature of the fluidics system which is likely an inherent safety feature 16. Complications with phaco on the mature and dense lenses frequently encountered in outreach settings are common 17,18.…”
Section: Discussioncontrasting
confidence: 68%
“…Concerns have been expressed about the fluidics in the eye during phacoemulsification and the impact on long-term postoperative complications. However, few studies have investigated these issues (1)(2)(3).…”
mentioning
confidence: 99%